Diversified agriculture leads to diversified diets: panel data evidence from Bangladesh - Mastura, Tamanna; Begum, Ismat Ara; Kishore, Avinash; Jackson, Tamara; Woodhill, Jim; Chatterjee, Kuhu; Alam, Mohammad Jahangir (Frontiers in Sustainable Food Systems, 2023)
Using three waves of nationally representative Bangladesh Integrated Household Survey data (BIHS- 2011-12, 2015 and 2018) and a panel data model, this study explored the linkages, if any, among household agricultural diversification and dietary diversity of farm households. Existing literature suggests that farm production diversification has the potential to influence the dietary diversity of farm households. Previous research measured diversification in terms of crop cultivation and livestock rearing, but this study follows a different perspective of measuring agricultural diversification by combining the three major sectors - crop, fish, and livestock production at the farm household level to assess the impact of such agricultural diversification on the dietary diversity of households. The balanced panel data allows us to reveal that agricultural production diversification has a statistically significant and positive impact on dietary diversity of farm households. Moreover, other important factors that impact agricultural diversification to improve dietary diversity, like women’s employment, market access, engagement with non-farm income sources, and access to information also have a strong association in improving the dietary status, food and nutritional security of households. Participation in the market helps farming households to become more commercially oriented but negatively affects the dietary diversification of the households. However, participation in non-farm activities was found to have a significant positive impact on dietary diversity, but not more than agricultural diversification. The findings suggest that nutrition-sensitive agricultural policy interventions focusing on providing support for diversified farming systems can directly increase the nutritionally enriched dietary intake, increasing the employability of women. Promoting market access through improved infrastructure should be recommended to improve the current scenarios.